Glycosylated amyloid‐like proteins in the structural extracellular polymers of aerobic granular sludge enriched with ammonium‐oxidizing bacteria. Issue 6 (31st March 2018) - Lin, Yuemei; Reino, Clara; Carrera, Julián; Pérez, Julio; van Loosdrecht, Mark C. M.
Abstract: A new type of structural extracellular polymers (EPS) was extracted from aerobic granular sludge dominated by ammonium‐oxidizing bacteria. It was analyzed by Raman and FTIR spectroscopy to characterize specific amino acids and protein secondary structure, and by SDS‐PAGE with different stains to identify different glycoconjugates. Its intrinsic fluorescence was captured to visualize the location of the extracted EPS in the nitrifying granules, and its hydrogel‐forming property was studied by rheometry. The extracted EPS is abundant with cross ß‐sheet secondary structure, contains glycosylated proteins/polypeptides, and rich in tryptophan. It forms hydrogel with high mechanical strength. The extraction and discovery of glycosylated proteins and/or amyloids further shows that conventionally used extraction and characterization techniques are not adequate for the study of structural extracellular polymers in biofilms and/or granular sludge. Confirming amyloids secondary structure in such a complex sample is challengeable due to the possibility of amyloids glycosylation and self‐assembly. A new definition of extracellular polymers components which includes glycosylated proteins and a better approach to studying them is required to stimulate biofilm research. Abstract : A new type of structural extracellular polymers (EPS) was extracted from aerobic granular sludge dominated by ammonium‐oxidizing bacteria. The extracted EPS is abundant with cross ß‐sheet secondary structure, contains glycosylated proteins/polypeptides, rich in tryptophan and forms hydrogel with high mechanical strength. The successful extraction and discovery of glycosylated proteins and/or amyloids further shows that conventionally used extraction and characterization techniques are not adequate for the study of structural extracellular polymers in biofilms and/or granular sludge, a new definition of extracellular polymers components which includes glycosylated proteins and a better approach to study them has to be developed in order to stimulate biofilm research.